Training and Assistance of Ecopreneurship for Senior High School Students in Surabaya - Wininatin Khamimah; Dewi Urip Wahyuni; Eka Yuliati; Tegowati (Indonesian Journal of Community Engagement, 2024)
The partner’s problems are: not all of students have the awareness to handle plastic waste well, and most students do not know how to utilize plastic waste into useful products. The solutions are: ecopreneurship training and assistance by making handicrafts from plastic waste. The output targets achieved are 1.) Partners understand the negative impacts of plastic waste on environment. 2.) Partners have the skills to utilize plastic waste into useful and marketable items. The method of implementing as follows: a. Conducting training at partner schools. Partners are given counseling on the negative impacts of plastic waste on environment and  trained on how to make handycrafts from plastic waste. b.) Conducting online assistance via video call, to find out the application of training materials and the obstacles faced by participants. Partners are enthusiastic, it increases their knowledge about economic potential of plastic waste.